2011
DOI: 10.1093/annonc/mdq548
|View full text |Cite
|
Sign up to set email alerts
|

Salvage radiotherapy in patients with recurrent or refractory primary or secondary central nervous system lymphoma after methotrexate-based chemotherapy

Abstract: Salvage RT is effective for patients with recurrent/refractory primary or secondary CNSL after initial MTX therapy. Having received five or more cycles of MTX before failure and CNSL limited to the brain at relapse are associated with longer OS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 15 publications
1
16
0
Order By: Relevance
“…In patients with primary or secondary CNS lymphoma who either develop a relapse after, or who are refractory to, CNS-directed chemotherapy, salvage RT can provide effective palliation and in some cases long-term disease control (35)(36)(37). In patients with relapsed or refractory CNS lymphoma and good performance status, HDT-ASCT has been used as salvage, although these programs have not typically included the use of RT (38)(39)(40)(41).…”
Section: Scenario 6: Relapsed/refractory Primary or Secondary Cns Lymmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with primary or secondary CNS lymphoma who either develop a relapse after, or who are refractory to, CNS-directed chemotherapy, salvage RT can provide effective palliation and in some cases long-term disease control (35)(36)(37). In patients with relapsed or refractory CNS lymphoma and good performance status, HDT-ASCT has been used as salvage, although these programs have not typically included the use of RT (38)(39)(40)(41).…”
Section: Scenario 6: Relapsed/refractory Primary or Secondary Cns Lymmentioning
confidence: 99%
“…Several studies have explored the role of salvage whole brain RT for patients with primary or secondary CNS lymphoma who either developed a relapse after or had refractory disease to CNS-directed chemotherapy (35)(36)(37). The median RT dose in these studies ranged from 36 to 40 Gy.…”
Section: Scenario 6: Relapsed/refractory Primary or Secondary Cns Lymmentioning
confidence: 99%
“…Median survival was 10.9 months and median PFS was 9.7 months. Khimani et al have reported an overall survival of 11.7 months with a CR of 50% with salvage WBRT in patients with primary or secondary CNSL 83. The median survival after salvage WBRT is comparable to the treatment with WBRT given as a first line treatment.…”
Section: Salvage Therapymentioning
confidence: 96%
“…Either HDT‐ASCT or WBRT should be considered in second remission if not undertaken as first‐line consolidation therapy. WBRT alone (median dose 36–40 Gy) can result in CR rates of 37–58% and a median survival of 10–16 months in radiotherapy‐naïve patients who are refractory to, or relapse after, HD‐MTX therapy (Nguyen et al , ; Hottinger et al , ; Khimani et al , ).…”
Section: Relapsed and Refractory Pcnslmentioning
confidence: 99%